The Effect of Pyrifenidone on Idiopathic Pulmonary Fibrosis - Shishuo Tian, Xin Li, Sijing Lu (Forest Chemicals Review, 1970)
System evaluation of pyrifenidone on idiopathic pulmonary fibrosis (IPF). From January 2018 and December 2019, 96 IPF patients were selected and divided into three groups: group A, only pyrifenidone used; group B, only acetylcysteine used; group C, pyrifenidone combined with acetylcysteine used. Meanwhile according to clinical features divided into mild-to-moderate IPF group and severe IPF group. And clinical curative effect, pulmonary function, HRCT score and adverse reactions were compared. Clinical curative effect, FEV1, FVC, DLCO, HRCT score were statistically significant different among three groups (P<0.05). Within mild-to-moderate group, group C was better than that of group A, group A was better than that of group B (P<0.05); Within severe group, group A and group C showed no statistical difference (P>0.05), but both were better than that of group B (P<0.05). Within mild-to-moderate group, adverse reactions had no statistical difference among three groups (P>0.05); within severe group, group C had the most adverse reactions. This experiment shows that: to mild-to-moderate patients, pyrifenidone combined with acetylcysteineis recommended overlooks the ketone with acetylcysteine therapy; to severe patients, pyrifenidone only is enough.